1998
DOI: 10.1038/bjc.1998.258
|View full text |Cite
|
Sign up to set email alerts
|

p53 Mutations in non-small-cell lung cancers occurring in individuals without a past history of active smoking

Abstract: Summary Accumulating evidence suggests that the p53 gene is a good target for molecular epidemiological studies. We previously reported an association between the presence of p53 mutations and lifetime cigarette consumption. Although over 675 p53 mutations have been reported in lung cancers in the literature thus far, very little is known about the nature of such changes in lung cancers in the absence of a smoking background. In the present study, we therefore analysed 69 non-small-cell lung cancer specimens f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…The loss of tumor suppressor p53 has not only been implicated as an early molecular event in the development of lung cancer in smokers, but also enables the acquisition of drug-resistant and metastatic phenotypes [12]. Activating mutations in intracellular signal transduction pathways like KRAS G12V lead to constitutive activation of proliferative signals which further enhance the aggressive behavior of p53 null lung tumors [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…The loss of tumor suppressor p53 has not only been implicated as an early molecular event in the development of lung cancer in smokers, but also enables the acquisition of drug-resistant and metastatic phenotypes [12]. Activating mutations in intracellular signal transduction pathways like KRAS G12V lead to constitutive activation of proliferative signals which further enhance the aggressive behavior of p53 null lung tumors [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Use of mutations in reporter genes, such as HPRT (Bailar, 1999;Hou et al, 1999) or GPA have been used, but it is better to identify mutation rates in cancer susceptibility genes such as p53 (Brennan et al, 1995;Valkonen and Kuusi, 1998) or K-ras (Scott et al, 1997;Slebos et al, 1991;Valkonen and Kuusi, 1998;Yakubovskaya et al, 1995). For p53, it has been reported that there is a dose response relationship between tobacco smoking and p53 mutations in general (Kondo et al, 1996) and for G to T transversions in particular (Kure et al, 1996;Takagi et al, 1998). Women have more G to T transversions than men for similar levels of smoking, even though men have p53 mutations more commonly (Kondo et al, 1996;Kure et al, 1996).…”
Section: Pathobiological Effects and The Clues To Etiologymentioning
confidence: 99%
“…In non-small cell lung cancer (NSCLC) about half of the tumours carry mutations in the p53 gene (Takagi et al, 1998). The prevalent type of mutation is G:C ¡ T:A transversion which is related to DNA adducts of benzo(a)pyrene from cigarette smoking Denissenko et al, 1996).…”
mentioning
confidence: 99%